2004
DOI: 10.1152/jn.00322.2004
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Corticothalamic Projections: Distinguishing Drivers From Modulators

Abstract: . We used a juvenile mouse thalamocortical slice preparation with whole cell recording to investigate synaptic properties of corticothalamic inputs from somatosensory cortex to the ventral posterior medial and posterior medial nuclei (98 cells). We compared these data to those obtained from activating retinal and cortical inputs to the lateral geniculate nucleus (8 cells), the former representing a prototypical driver input and the latter, a typical modulator. Retinogeniculate activation evoked large, all-or-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
291
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 244 publications
(325 citation statements)
references
References 50 publications
(43 reference statements)
27
291
1
Order By: Relevance
“…The speed is necessarily related to the structure, which is why these points are combined. While direct evidence is not available concerning the anatomical arrangement of synapses on MD neurons comparable to that in other thalamic regions (e.g., the pulvinar, Guillery, 1995;Reichova and Sherman, 2004), there are a few observations that suggest that the SC to MD synapses are strong and secure, which make them reasonable candidates for drivers. First of all, it was found that single pulse stimulation in the SC activated MD neurons with short latency (median 1.4 ms, including a presumed synaptic delay of only 0.57 ms) and required normal current thresholds for this type of study (mean 264 mA).…”
Section: Sc As a Driver Input To MDmentioning
confidence: 99%
“…The speed is necessarily related to the structure, which is why these points are combined. While direct evidence is not available concerning the anatomical arrangement of synapses on MD neurons comparable to that in other thalamic regions (e.g., the pulvinar, Guillery, 1995;Reichova and Sherman, 2004), there are a few observations that suggest that the SC to MD synapses are strong and secure, which make them reasonable candidates for drivers. First of all, it was found that single pulse stimulation in the SC activated MD neurons with short latency (median 1.4 ms, including a presumed synaptic delay of only 0.57 ms) and required normal current thresholds for this type of study (mean 264 mA).…”
Section: Sc As a Driver Input To MDmentioning
confidence: 99%
“…Examples of these higher order relays are the pulvinar for vision, the posterior nucleus for somesthesia, and the magnocellular portion of the medial geniculate nucleus for hearing (Sherman andGuillery, 1996, 2006;Sherman, 2005). Central to this view is evidence showing that synaptic properties of corticothalamic input from layer 5 to higher order nuclei share the same driver properties measured anatomically, physiologically, and pharmacologically as do retinogeniculate input and medial lemniscal input to the ventral posterior nucleus (Schwartz et al, 1991;Hoogland et al, 1991;DeschĂȘnes et al, 1994;Ojima, 1994;Rockland, 1996;Rouiller and Welker, 2000;Bartlett et al, 2000;Guillery et al, 2001;Li et al, 2003b;Reichova and Sherman, 2004). These higher order relays have only been recently recognized, and they seem to occupy the majority of thalamus (Sherman and Guillery, 2006).…”
mentioning
confidence: 98%
“…Do they align topographically with the anisotropic frequency organization in the ICc and MGBv (1, 2)? Do excitatory and inhibitory inputs arise from the same loci, or are they topographically segregated?To investigate these issues of auditory tectothalamic organization, we developed an in vitro tectothalamic slice preparation in the mouse containing parts of the ascending pathways to the MGB.Whole-cell recordings of MGB neurons in response to photostimulation in the IC with caged glutamate were used to map the topography of excitatory and inhibitory inputs and to identify loci for subsequent electrical stimulation as well as to identify these tectothalamic synaptic inputs as drivers or modulators (5,8,12). …”
mentioning
confidence: 99%
“…Whole-cell recordings of MGB neurons in response to photostimulation in the IC with caged glutamate were used to map the topography of excitatory and inhibitory inputs and to identify loci for subsequent electrical stimulation as well as to identify these tectothalamic synaptic inputs as drivers or modulators (5,8,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation